2022
DOI: 10.1111/jocs.16550
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin D supplementation on postoperative atrial fibrillation after coronary artery bypass grafting in patients with vitamin D deficiency

Abstract: Introduction: Postoperative atrial fibrillation (POAF) as a common complication of coronary artery bypass grafting (CABG) surgery is associated with increased mortality and morbidity rates. Vitamin D deficiency increases the prevalence of POAF; however, the effects of vitamin D supplementation on the incidence of POAF have not yet been completely elucidated. Methods: In this prospective, open-label, randomized clinical trial the level of 25-hydroxy vitamin D (25(OH) D) was measured in patients undergoing CABG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…7 8 Three studies (37.5%) detected significant reduction in postoperative atrial fibrillation (POAF) by vitamin D therapy. 9 10 Two studies (25%) detected significant reduction in inotrope requirement postoperatively compared with control group. 11 One study (12.5%) observed marked reduction in duration of ICU and hospital stay in vitamin D supplementation group compared with control.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…7 8 Three studies (37.5%) detected significant reduction in postoperative atrial fibrillation (POAF) by vitamin D therapy. 9 10 Two studies (25%) detected significant reduction in inotrope requirement postoperatively compared with control group. 11 One study (12.5%) observed marked reduction in duration of ICU and hospital stay in vitamin D supplementation group compared with control.…”
Section: Resultsmentioning
confidence: 96%
“…POAF: The present systemic review detected three RCTs showing reduction in POAF by vitamin D supplementation. 9 10 19 However, Sahu et al 8 did not find any difference. Conflicting results were seen by a prospective cohort study by Ohlrogge et al for POAF with VDD.…”
Section: Discussionmentioning
confidence: 91%
“…In the study, which included 196 patients, the patients were divided into two groups as those with and without vitamin D supplementation. At the end of the study, the rate of PoAF was found to be significantly higher in patients who did not receive vitamin D supplementation (9.68% vs. 20.39%, p = .038) 10 . In this study, postoperative electrocardiography follow‐ups were performed with continuous telemetry.…”
Section: Commentarymentioning
confidence: 91%
“…In a recent metaanalysis and systematic review study, it was concluded that vitamin D deficiency increases the risk of PoAF. 9 In this issue of the Journal of Cardiac Surgery, in a study conducted by Talasaz et al, 10 the effect of preoperative oral vitamin D supplementation on PoAF in patients with vitamin D deficiency who underwent CABG was investigated. In the study, which included 196 patients, the patients were divided into two groups as those with and without vitamin D supplementation.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation